2020
DOI: 10.1016/j.encep.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing chlorpromazine to treat COVID-19: The reCoVery study

Abstract: Objectives. -The ongoing COVID-19 pandemic has caused approximately 2,350,000 infections worldwide and killed more than 160,000 individuals. In Sainte-Anne Hospital (GHU PARIS Psychiatrie & Neuroscience, Paris, France) we have observed a lower incidence of symptomatic forms of COVID-19 among patients than among our clinical staff. This observation led us to hypothesize that psychotropic drugs could have a prophylactic action against SARS-CoV-2 and protect patients from the symptomatic and virulent forms of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(137 citation statements)
references
References 34 publications
4
129
1
3
Order By: Relevance
“…The approach through drug repurposing offers little hope, but still does not show the best results. However, the basic problem from repurposing the existing drugs is the raising of adverse effects in a long-term usage (Harrison, 2020 ;Plaze, et. al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The approach through drug repurposing offers little hope, but still does not show the best results. However, the basic problem from repurposing the existing drugs is the raising of adverse effects in a long-term usage (Harrison, 2020 ;Plaze, et. al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorpromazine, a dimethylamine derivative of phenothiazine used in the treatment of acute and chronic psychoses 4 , has been suggested as potential effective treatment for Covid-19 on the grounds of its antiviral and anti-inflammatory effects 5 . Specifically, several in-vitro studies [6][7][8] showed that chlorpromazine reduces viral replication of coronavirus-229E, MERS-CoV et SARS-CoV-1, possibly through the inhibition of clathrin-mediated endocytosis 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several mouse models of sepsis [11][12][13][14] suggest that this medication is associated with a decrease in pro-inflammatory cytokines, including IL-2, IL4, IFN alpha, TNF, and GM-CSF, and an increase of the anti-inflammatory cytokine IL-10. Short-term use of chlorpromazine is generally well tolerated 5,15 , although side effects can occur, including QT interval prolongation, extrapyramidal symptoms, dry mouth, dizziness, urine retention, blurred vision, constipation, and hyperprolactinemia 5,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we identified a dozen of host factors that are bound by coronavirus proteins and functionally modulated by compounds selected from antiviral screens, giving hints to explain the inhibition of coronavirus replication by these drugs. Among these molecules is chlorpromazine, an antipsychotic drug that is currently evaluated in a clinical trial against SARS-CoV-2 [78]. In conclusion, this work has highlighted the importance of several neglected coronavirus-host interactions that deserve to be further investigated.…”
Section: Discussionmentioning
confidence: 91%